Pengaturan Pengupahan Tenaga Kerja UMKM Berdasarkan Undang-Undang Nomor 6 Tahun 2023 Tentang Cipta Kerja Menurut Perspektif Hak Asasi Manusia - Didi Nazmi (LPPM Universitas Ekasakti Padang, 2023)
From issues of protection, wages, welfare, industrial relations disputes, labor development and inspection. The philosophy of the Labor Law in force in Indonesia is that national development is carried out in the context of the complete development of Indonesian people and the development of Indonesian society as a whole to create a prosperous, just, prosperous, equitable society, both materially and spiritually based on Pancasila and the Constitution of the Republic of Indonesia. Indonesia in 1945. Wage arrangements for MSME workers which are only determined based on an agreement will have the potential for irregularities in wages. Even with the arrangement of wage payments to see indications of economic conditions by the government, the wages of MSME workers should be determined like other workers. This research is a normative legal research (doctrinal research) with a Statutes Approach and a conceptual approach. The results of this study explain first, special arrangements for the Indonesian government's MSMEs wages aim to realize quality employment development. Determination of wages in the MSME sector is not only based on agreements and the average consumption of the community. Instead, employers are required to compile and implement a pay scale structure with due regard to financial capabilities and productivity. Second, the legal consequence of the existence of Perpu 2/2022 creates a decent wage for MSME workers. Fulfillment of wages for MSME workers provides legal certainty and is able to guarantee their survival based on the principle of balance.